2023
DOI: 10.3390/cells12020246
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Exposure to Simulated Microgravity, Ionizing Radiation, and Cortisol on the In Vitro Wound Healing Process

Abstract: Human spaceflight is associated with several health-related issues as a result of long-term exposure to microgravity, ionizing radiation, and higher levels of psychological stress. Frequent reported skin problems in space include rashes, itches, and a delayed wound healing. Access to space is restricted by financial and logistical issues; as a consequence, experimental sample sizes are often small, which limits the generalization of the results. Earth-based simulation models can be used to investigate cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 113 publications
0
6
1
Order By: Relevance
“…Although we did not find a significant delay in migration in simulated microgravity-exposed cells, in a previous study, a delayed migration in fibroblasts exposed to simulated microgravity was found 11 , 12 . A possible explanation for this seemingly contradiction might be found in our study design, as we were only able to measure migration of cells after fixation at a specific time point.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Although we did not find a significant delay in migration in simulated microgravity-exposed cells, in a previous study, a delayed migration in fibroblasts exposed to simulated microgravity was found 11 , 12 . A possible explanation for this seemingly contradiction might be found in our study design, as we were only able to measure migration of cells after fixation at a specific time point.…”
Section: Discussioncontrasting
confidence: 95%
“…Fibroblasts, which are the major cellular component of the dermis, play a vital role in wound healing by migrating to the side of the wound and interacting with the ECM 9 , 10 . Earth-based simulation studies have verified the notion of delayed wound healing and showed decreased migration capabilities in fibroblasts after exposure to simulated microgravity 11 , 12 . Delay in the wound-healing process can also be found during periods of chronic psychological stress 13 , 14 .…”
Section: Introductionmentioning
confidence: 76%
“…Also, skin cells are affected by spaceflight. Fibroblast function under different combinations of simulated space stressors was assessed by Radstake et al Results show interactions between different spaceflight stressors affecting different cellular processes [42]. With regard to the immune system, several in vitro studies using different cell types have been focusing on the effects of simulated microgravity on the DNA damage response (DDR) to ionizing radiation [43,44], which can be translated into a higher risk for astronauts.…”
Section: Discussionmentioning
confidence: 99%
“…These results seem to indicate that hydrocortisone can influence the sensitivity of Jurkat cells to ionizing radiation. Radstake et al also showed that the addition of cortisol to fibroblasts altered their response to simulated microgravity and radiation exposure [42]. Chronic stress has also been suggested to have implications on the outcome of radiotherapy treatments through the suppression of the immune system [48].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological effects of altered gravity environments on the human body are wide and varied. They include ocularvestibular changes, blood clotting and wound healing dysfunction, increased cellular turnover and the more widely appreciated cardiovascular and musculo-skeletal changes [45][46][47]. There is good evidence to support gene dysregulation, immune dysfunction and disturbances in cellular and immune signaling as the contributors to some of these effects [48].…”
Section: The Physiological Effects Of Altered Gravity Environmentsmentioning
confidence: 99%